DETERMINANTS OF FIRM-LEVEL GROWTH: LESSONS FROM THE CZECH REPUBLIC, HUNGARY, AND POLAND (The South East European Journal of Economics and Business, 2023)
This paper examines the determinants of firm-level growth based on three eastern European countries – the Czech Republic, Hungary, and Poland. We investigate whether there exist common firm-level characteristics that play a significant role in determining firm-level performance across the three countries, and whether development in financial markets can facilitate the growth of individual firms, particularly for firms that require external financing (borrowing). Our empirical analysis shows that in the case of Poland, firm-level characteristics, such as firm age and firm size, turn out to be significant, and that the role of these factors on the sales growth of firms is quite consistent with the findings in the existing literature. The same firm-level characteristics do not appear to be significant in the cases of Czechia and Hungary, which suggests that these factors play a different role in the firm-level growth of these countries. However, a firm’s access to external financing matters for the determining the firm’s growth and its development of financial markets, which enables the firm to have easier access to external sources of financing, thereby especially facilitating the growth of the individual firm that might need external funds. Our findings provide additional empirical evidence on the existing literature that emphasizes the positive impact of financial development on the individual firms’ growth based on a cross-country analysis.